Defining Dignity and Its Place in Human Rights. Issue 1 (1st January 2014) - Michael, Lucy
Abstract The concept of dignity is widely used in society, particularly in reference to human rights law and bioethics. Several conceptions of dignity are identified, falling broadly within two categories: full inherent dignity (FID) and non-inherent dignity (NID). FID is a quality belonging equally to every being with full moral status, including all members of the human natural kind; it is permanent, unconditional, indivisible and inviolable. Those beings with FID ought to be treated deferentially by others by virtue of their belonging to a noble caste. FID grounds fundamental human rights, such as the rights to freedom and equality. The concept of dignity forms a network of interconnected ideas related to worth and value particularly within legal and ethical discourse; it is a rich and meaningful concept, irreducible to one or two quasi-legal principles. Fundamentally, dignity matters because it forms the foundation of civilized society; without it, serious abuse of people is more likely to occur.